2019
DOI: 10.1109/tccn.2019.2911005
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network Prediction-Based Adaptive Mode Selection Scheme in Full-Duplex Cognitive Networks

Abstract: We propose a neural network (NN) predictor and an adaptive mode selection scheme for the purpose of both improving secondary user's (SU's) throughput and reducing collision probability to the primary user (PU) in full-duplex (FD) cognitive networks. SUs can adaptively switch between FD transmissionand-reception (TR) and transmission-and-sensing (TS) modes based on the NN prediction results for each transmission duration. The prediction performance is then analysed in terms of prediction error probability. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In [205], a Deep Q-Network (DQN) is proposed to predict and select a free channel for WSNs. In [208], the authors design a NN predictor to predict PUs future activity based on past channel occupancy sensing results, with the goal of improving secondary users (SUs) throughput while alleviating collision to primary user (PU) in full-duplex (FD) cognitive networks.…”
Section: Medium Access Control (Mac) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In [205], a Deep Q-Network (DQN) is proposed to predict and select a free channel for WSNs. In [208], the authors design a NN predictor to predict PUs future activity based on past channel occupancy sensing results, with the goal of improving secondary users (SUs) throughput while alleviating collision to primary user (PU) in full-duplex (FD) cognitive networks.…”
Section: Medium Access Control (Mac) Analysismentioning
confidence: 99%
“…• MAC identification [194][195][196][197][198][199] • Wireless interference detection at packet level [200][201][202][203] • Spectrum prediction [204][205][206][207][208][209] Network prediction…”
mentioning
confidence: 99%
“…• MAC identification [187][188][189][190] • Wireless interference identification [191][192][193][194] • Spectrum prediction [195][196][197][198][199][200] Network prediction…”
Section: Mac Analysismentioning
confidence: 99%
“…e following is the use of neural network technology to solve the problem [8,9]. Geoffrey Hinton obtained some surprising results on MNIST and showed that the acoustic model of a frequently used commercial system can be significantly improved by distilling the knowledge in the model set [10,11]. Yang Shen's program has been trained to extract trunk.…”
Section: Introductionmentioning
confidence: 99%